Identification of a prosurvival neuroprotective mitochondrial peptide in a mammalian hibernator. (6th August 2019) - Szereszewski, Kama E.; Storey, Kenneth B.
Abstract: Hibernation requires the intricate regulation of physiological and biochemical adaptations to facilitate the decrease in metabolic rate and activation of prosurvival factors needed for winter survival. Mitochondria play important roles in eliciting these responses and in coordinating the required energy shifts. Herein, we report the presence of a novel mitochondrial peptide, s‐humanin, in the hibernating 13‐lined ground squirrel, Ictidomys tridecemlineatus . S‐humanin was shown to have strong structural and sequence similarities to its human analogue, humanin—a powerful neuroprotective mitochondrial peptide. An assessment of the protein and gene expression levels of this peptide in ground squirrels revealed stark tissue‐specific regulatory responses whereby transcript levels increased in brain cortex, skeletal muscle, and adipose tissues during hibernation, suggesting a protective torpor‐induced activation. Accompanying peptide measurements found that s‐humanin levels were suppressed in liver of torpid squirrels but enhanced in brain cortex. The enhanced transcript and protein levels of s‐humanin in brain cortex suggest that it is actively involved in protecting delicate brain tissues and neuronal connections from hibernation‐associated stresses. We propose that this squirrel‐specific peptide is involved in modulating tissue‐specific cytoprotective functions, expanding its role from human‐specific neuroprotection to environmental stress protection. Significance of the study: Understanding the molecular mechanisms, which protect against oxidative stress in a model hibernator such as the ground squirrel, could be pivotal to the regulation of cytoprotection. This study expands on our knowledge of metabolic rate depression and could suggest a potential role for humanin therapy in neurodegenerative diseases.